Biological Potential Of Sequentially Extracted Leaf Extracts Of Wrightia Tinctoria (Roxb.) R. Br. (Applied Biological Research, 2023)
Wrightia tinctoria has long been exploited for its therapeutic potential and has proved an effective natural medicine for various disorders and illnesses. This  study was aimed to assess the phytochemical and biological activity of W.  tinctoria extracts that would support both the traditional and pharmaceutical  uses of its leaves. Following the consecutive extractions of fresh W. tinctoria leaves using petroleum ether, chloroform, methanol, and aqueous solvents in  sequence; several phytochemicals were discovered. The study revealed the  presence of alkaloids, flavonoids, tannins, beta-cyanin, fats and fixed oil in the  extracts. The antioxidant activity of extracts using DPPH (2,2-diphenylpicryl hydrazyl) assay, antibacterial activity (disc diffusion assay), and the extract’s apoptotic character (acridine orange and ethidium bromide staining) were also  assessed. The study revealed relatively high bioactivity in chloroform extract.  The chloroform extract showed good antioxidant (IC50 296 µg mL-1), anti bacterial and anticancer (100 µg mL-1) activity in SKBr3 cell lines. It was  purified using column chromatography. The prominent fraction was chosen and  characterized by GCMS analysis. Many active biomolecules with significant  biological activity were found. Further studies are needed to understand the  mechanism of action of these potent compounds noticed in W. tinctoria extract.
Keywords: Bioactivity; characterisation; purification; Wrightia tinctoria